2022
DOI: 10.1371/journal.pone.0269092
|View full text |Cite
|
Sign up to set email alerts
|

State-led agricultural subsidies drive monoculture cultivar cashew expansion in northern Western Ghats, India

Abstract: Agricultural commodity production constitutes an important livelihood source for farmers but significantly contributes to tropical deforestation and biodiversity loss. While the socioecological effects of agricultural commodities such as palm oil, cocoa and coffee are well studied, the effects for commodities such as cashew (Anacardium occidentale) have received less attention. Global cultivated area for cashew increased rapidly from 526,250 ha in 1980 to ~5.9 million ha in 2018. India is the world’s second la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…If the populations of females, which occur in much lower densities than males, are impacted, it will result in the shrub frog populations crashing. Moreover, we demonstrate that Pseudophilautus , which has been thought to be a generalist and resilient species (Sankararaman et al, 2021), is negatively impacted by cashew plantations, which are rapidly increasing in the landscape (Rege & Lee, 2022) and currently occupy almost a third of the geographic area of the Dodamarg and Sawantwadi Taluks where the study was conducted. This is an important consideration for the IUCN Redlist Status assessment, which recently downlisted these two endemic species from Threatened category to Least Concern (IUCN SSC Amphibian Specialist Group, 2021).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…If the populations of females, which occur in much lower densities than males, are impacted, it will result in the shrub frog populations crashing. Moreover, we demonstrate that Pseudophilautus , which has been thought to be a generalist and resilient species (Sankararaman et al, 2021), is negatively impacted by cashew plantations, which are rapidly increasing in the landscape (Rege & Lee, 2022) and currently occupy almost a third of the geographic area of the Dodamarg and Sawantwadi Taluks where the study was conducted. This is an important consideration for the IUCN Redlist Status assessment, which recently downlisted these two endemic species from Threatened category to Least Concern (IUCN SSC Amphibian Specialist Group, 2021).…”
Section: Discussionmentioning
confidence: 90%
“…However, a recent study suggests chronic human disturbance has converted evergreen forests into deciduous forests across low and high elevations (Biswas et al, 2024). The area has witnessed significant conversion of private forests into cashew, rubber, and pineapple plantations in recent decades (Rege & Lee, 2022; Munje & Kumar, 2022; Biswas et al, 2023). Within our study area, five species of Rhacophorid frogs are found, including the three species of shrub frogs - Pseudophilautus amboli , P. wynaadensis , and Raorchestes bombayensis - although P .…”
Section: Sampling Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We studied in the northern Western Ghats of Maharashtra state, India, between January and May 2022. While the forests in the southern Western Ghats have been mostly converted to tea, coffee and rubber, the privately-owned forests of northern Western Ghats are being rapidly converted to mango, cashew, and rubber (Rege & Lee, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Businesses differentiate themselves from one another through their internal core knowledge and unique capabilities, which are valuable, difficult for competitors to imitate, and non-replicable. Their profitability and competitive advantage stem from their enterprise heterogeneity, which is fueled by factors like productivity, enterprise size, ownership, and industry (Jia et al, 2021;Li et al, 2023;Rege & Lee, 2022;Zaman & Zaccour, 2021).…”
Section: Variability In Enterprisementioning
confidence: 99%